Differential Packaging Into Outer Membrane Vesicles Upon Oxidative Stress Reveals a General Mechanism for Cargo Selectivity - Orench-Rivera, Nichole; Kuehn, Meta J. (Frontiers in Microbiology, 2021)
Selective cargo packaging into bacterial extracellular vesicles has been reported and implicated in many biological processes, however, the mechanism behind the selectivity has remained largely unexplored. In this study, proteomic analysis of outer membrane (OM) and OM vesicle (OMV) fractions from enterotoxigenic E. coli revealed significant differences in protein abundance in the OMV and OM fractions for cultures shifted to oxidative stress conditions. Analysis of sequences of proteins preferentially packaged into OMVs showed that proteins with oxidizable residues were more packaged into OMVs in comparison with those retained in the membrane. In addition, the results indicated two distinct classes of OM-associated proteins were differentially packaged into OMVs as a function of peroxide treatment. Implementing a Bayesian hierarchical model, OM lipoproteins were determined to be preferentially exported during stress whereas integral OM proteins were preferentially retained in the cell. Selectivity was determined to be independent of transcriptional regulation of the proteins upon oxidative stress and was validated using randomly selected protein candidates from the different cargo classes. Based on these data, a hypothetical functional and mechanistic basis for cargo selectivity was tested using OmpA constructs. Our study reveals a basic mechanism for cargo selectivity into OMVs that may be useful for the engineering of OMVs for future biotechnological applications.